1998
DOI: 10.2166/wst.1998.0765
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of contaminated sediments in Oslo harbour, Norway

Abstract: During the past 60-70 years, contaminated sediments from local rivers have been settling in the harbour basin of Oslo. This contamination, combined with that from other harbour activities, has developed into a serious pollution problem with both organic and inorganic contaminants. Since 1992 dredging activities have been restricted until the effect of dredging was determined and a safe disposal was found for the sediments. Because of this restriction, a conflict situation arose in terms of decreasing sailing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In fact, one of the highest measured water column PCB concentrations during the pilot study occurred during a wind-driven event when no dredging was occurring (Nelson and Hanson, 1991). This finding is consistent with other studies which demonstrated that weather, boat traffic, and natural flow variability can increase resuspension more than dredging operations (Hauge et al, 1998;Whyte and Kirchner, 2000;Ko and Baker, 2003).…”
Section: Net Transportsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, one of the highest measured water column PCB concentrations during the pilot study occurred during a wind-driven event when no dredging was occurring (Nelson and Hanson, 1991). This finding is consistent with other studies which demonstrated that weather, boat traffic, and natural flow variability can increase resuspension more than dredging operations (Hauge et al, 1998;Whyte and Kirchner, 2000;Ko and Baker, 2003).…”
Section: Net Transportsupporting
confidence: 93%
“…However, there is an ongoing debate about the potential negative effects (e.g., resuspension and transport of contaminants) and positive benefits (e.g., permanently removing contaminants from an aquatic system) of dredging contaminated sediments (den Besten et al, 2000;Voie et al, 2002;Weston et al, 2002). To address these questions, several dredging projects have conducted pilot studies and instituted environmental monitoring programs during and immediately after dredging (Hauge et al, 1998;Vale et al, 1998). Several of these projects showed that remedial dredging could be conducted safely with proper controls (Nelson and Hansen, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In (Detzner et al, 1998) a pilot plant is introduced which was constructed to physically separate uncontaminated sand-from contaminated silt fractions of dregded material of Hamburg harbours. The harbour and waterways of Hamburg are regularily dregded to maintain a sufficient water depth for shipping traffic (Hauge et al, 1998). Therefore, mostly chemical analysis alone is used for remediation success evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Boundary conditions. Taken together, past studies indicate that the elevated levels of PCBs in the Inner Oslofjord are a problem of local contamination caused by inputs of PCBs from the atmosphere, rivers, and direct discharges [5,7,28,39]. It thus seems safe to assume that the Inner Oslofjord has been a net source of PCBs to the Outer Oslofjord [5] (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Riverine inflows. Past studies had indicated that rivers discharge PCBs to the fjord [27,28,39]. For the model calculations, we relied on information presented by Holtan et al [27] for five major rivers draining into the fjord.…”
Section: Methodsmentioning
confidence: 99%